Vehicles Speed in Platoon, Case Study Padang - Bukittinggi Road - Ramayanti, Sri; Adji, Bayu Martanto; yosritzal, yosritzal; Gunawan, Hendra (Civil Engineering Departement, Andalas University, 2021)
The increase in vehicle ownership number will affect the increase in traffic flow, which will usually result in congestion on the road network. This phenomenon causes vehicles to tend to travel close to one another (platoon). Characteristics used in describing the platoon phenomenon are the distance between vehicles (headway), average speed, and the number of vehicles in the platoon. This study is to analyzes the effect of variations in the leader and platoon length on vehicle speed. This research was conducted on Padang â€“ Bukittinggi Road. Based on the Decree of the Minister of PUPR No: 248/KPTS/M/2015, Padang - Bukittinggi Road is categorized as a primary arterial road. This research used the primary data, a field survey, by recording vehicle traffic flow (traffic platoon) for two days. A distance of 50 meters is taken to determine the speed, and the time is measured with a stop program. The average headway on weekdays is 1.32 seconds and on holidays is 1.47 seconds. The size of the platoon and the type of platoon leader have a significant effect on the average speed of the vehicle in the platoon if the headway isÂ â‰¤ 2 seconds. At the addition of one vehicle in the platoon, which can change the vehicle's average speed, follows the equation y = -4.30x + 67.09.